Penerapan Model Pembelajaran Daring Untuk Memenuhi Target Perkuliahan di Masa Pandemik Pada Mahasiswa Pg-Paud Fip Unima - Threesje Tolukun (Jurnal Ilmiah Wahana Pendidikan, 2021)
Learning media available online are very diverse and constantly evolving. The existence of this media is very helpful for lecturers in the learning process in class without being preoccupied with the activity of making the media itself. Based on the results of observations made on PG-PAUD FIP UNIMA study program students, students have used various applications from universities as media in the learning process. Lecturers use online learning models as media in delivering lecture material. The formulation of the problem in this study, namely how to apply the online learning model during a pandemic for PG-PAUD FIP UNIMA Study Program students so that they can meet lecture targets and what are the problems encountered in implementing the online learning model for PG-PAUD FIP UNIMA students. The purpose of this study is to find out how to apply the online learning model, to find out the problems encountered in implementing the online learning model for PG-PAUD FIP UNIMA students. This research is a qualitative research with descriptive analysis techniques. Analysis of research data obtained from the process of searching and compiling systematically, data obtained from observations, interviews and the field, namely data collection, data reduction, data presentation, conclusions and verification. The results of the study show that the application of the online learning model in the PG-PAUD FIP UNIMA Study Program is by using several types of applications, using lesson plans according to the curriculum and evaluating written worksheets. The inhibiting factors in implementing online learning are the lack of effectiveness and efficiency of time, the lack of student enthusiasm and the lack of student understanding of the material. The supporting factors for online learning are that the campus facilitates wifi for lecturers while on campus, and students are given free internet quota.